Territorial strategies for productive transformation. Reflection from the case of the Basque Country (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2016)
This paper reviews the recent literature on territorial strategy, showing its origins, the differences between business and territorial strategies, the distinctive features of the research and innovation smart specialisation strategies (i.e. the thematic priorities and entrepreneurial discovery processes) and the ways and mechanisms (modernization, extending, radical foundation and combination) for the transformation of the production structure that all territorial strategies should try to achieve. Then, in order to illustrate all this and draw some lessons that could guide the Spanish regions’ territorial strategies for the transformation of their production systems, the paper analyses the Basque Country’s development strategies implemented since the early eighties, and particularly its current smart specialisation strategy.
Keywords: territorial strategy; smart specialization; diversification; vertical priorities; Basque Country.